Banks' lending behaviour under repressed financial regulatory environment: In the context of Myanmar. Issue 1 (5th February 2018) - Win, Sandar
Abstract : Purpose: Regulatory authorities in Myanmar are increasing banks' independence in providing loans to facilitate better financial resource allocations. On the other hand, not only in the USA but also among European countries, policymakers are designing regulations that could reduce banks' autonomies in risk management and decrease risk taking behaviour. These governments have made policy interventions in their banking sectors which could be identified as repressive policies. They are commonly justified as macro-prudential regulations rather than financial repression. However, the authors are yet to understand as to what extent regulations need to be tightened or loosened up to reach optimal risk-taking behaviour. Using Myanmar as an example where the extreme form of governmental interventions and prudential regulations exists, this paper aims to identify the effectiveness of such policies. Design/methodology/approach: This paper relies on a case study of the Myanmar's Banking Sector. The paper adopts of the synthesis of institutional theory and Oliver's strategic response to identify how banks respond to repressive financial policies. The empirical evidence is collected through conducting 16 interviews including banks' general managers, deputy chairmen and loan officers. Afterwards, the authors analysed the data using categorical thematic analysis with the assistance of NVIVO. Findings: First of all, the extent to which repressive financial measures enforced on banks differ depending on their political affiliations and ownership structures. Second, though repressive policies were enforced on banks to curb risk taking behaviour among banks and maintain financial stability, Myanmar banks themselves had inherent nature of risk aversion towards lending. Third, in Myanmar, financial repression does not always mean banks need to compromise their efficiency in profit maximisation to achieve legitimacy from the regulatory authorities. If the formal constraints were not in line with economic actors' internal objectives, a different set of rules of the game were formed. Originality/value: This paper provides new evidences for the controversial subject on financial repression and liberalisation through analysing micro level data of banks' lending practice rather than using aggregate macro-level data. Bank-level information provides banks' concerns, challenges and their loan assessment process while operating under repressive financial policies. This study is also unique in the sense that it is contributing to the limited academic literature on Myanmar's financial system. It represents the last surviving case of repressed financial system and the presence governmental interventions and prudential regulations. Hence, it was used as an example to identify the effectiveness of such policies.